Ketuhanan dalam Era Pluralisme : Relevansi Sila Pertama Pancasila dalam Kebijakan Negara - Hamdan, Nur; Masyitoh, Siti (Majelis: Jurnal Hukum Indonesia, 2025)
This study aims to examine the relevance of the first principle of Pancasila in supporting diversity and the role of the state in maintaining harmony of diversity in Indonesia. The method used is a qualitative approach with a descriptive-analytical method. Based on the results of the analysis, it can be concluded that the First Principle, "Belief in the One and Only God," supports diversity in Indonesia by emphasizing the value of inclusivity that promotes tolerance, respect, and recognition of various religions, cultures, and traditions. This supports the principle of Bhinneka Tunggal Ika, making diversity a unifying force for the nation. In addition, the state has a strategic role in maintaining harmony of diversity through regulations that ensure religious freedom, law enforcement against intolerance, and the development of multicultural education. Although challenges such as radicalism and intolerance remain, collaboration between the government and society is essential to realize social harmony in accordance with the values of the First Principle in Pancasila.